2005
DOI: 10.1055/s-2005-864100
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Magnolol and Honokiol are Mediated through Inhibition of the Downstream Pathway of MEKK-1 in NF-κB Activation Signaling

Abstract: Propionibacterium acnes, an anaerobic pathogen, plays an important role in the pathogenesis of acne and seems to initiate the inflammatory process by producing proinflammatory cytokines. In order to demonstrate the anti-inflammatory effects and action mechanisms of magnolol and honokiol, several methods were employed. Through DPPH and SOD activity assays, we found that although both magnolol and honokiol have antioxidant activities, honokiol has relatively stronger antioxidant activities than magnolol {[for DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
86
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 14 publications
(14 reference statements)
3
86
0
Order By: Relevance
“…Honokiol also inhibited the TNFinduced COX-2 promoter activity, which is regulated by NF-nB (30). These results agree with a recent report (5) showing that honokiol inhibits NF-nB luciferase reporter activity. We also found that honokiol suppressed NF-nB activation induced by overexpression of TNFR1, TRADD, TRAF2, NIK, and IKK plasmids but had no effect on activation induced by p65 plasmid.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Honokiol also inhibited the TNFinduced COX-2 promoter activity, which is regulated by NF-nB (30). These results agree with a recent report (5) showing that honokiol inhibits NF-nB luciferase reporter activity. We also found that honokiol suppressed NF-nB activation induced by overexpression of TNFR1, TRADD, TRAF2, NIK, and IKK plasmids but had no effect on activation induced by p65 plasmid.…”
Section: Discussionsupporting
confidence: 83%
“…The suppression of invasion (32) and angiogenesis (33) reported previously agrees with the results reported here. The inflammatory cytokines TNF and interleukin-8, both known to promote angiogenesis, have also been shown to be down-regulated by honokiol (4,5). The down-regulation of nitric oxide synthesis by honokiol reported previously (4) also likely occurs through the suppression of NF-nB activation as reported here.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Magnolia officinalis reportedly has antimutagenic, 8) hepatocytic protective, 9,10) neuroprotective, 11) and anti-inflammatory effects. 12) Pueraria lobata reportedly has antimutagenic, antidiabetic and antioxidant effects. [13][14][15] Glycyrrhiza uralensis has detoxification, antiulcer, antiinflammation, antiviral, antiatherogenic, and anticarcinogenic effects, 16) and Euphorbia pekinensis has for antiviral and cytotoxic activities.…”
mentioning
confidence: 99%
“…The biphenolic compounds were initially thought of as the major active compounds of the plants. Honokiol has several pharmacological benefits, including antimicrobial (Clark et al, 1981), anti-inflammatory (Liou et al, 2003a;Lee et al, 2005;Chiang et al, 2006), antioxidative (Liou et al, 2003b;Sheu et al, 2008), anxiolytic (Kuribara et al, 1998;Kuribara et al, 2000), antiangiogenic (Liou et al, 2003c;Li et al, 2008), and antineoplastic effects (Battle et al, 2005;Sheu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%